1832 Conn. Acts 391, An Act Regulating the Mode Of Keeping Of Gunpowder, Chap. 25, § 1-2 - (:unkn) unknown (General Publisher, 1832)
Empowered the select-men of each and eer town within the state to remove quantities of gunpowder from the limits of their town to a place specified in the select-men's order as safe and convenient.
--
Keywords: GUN POWDER